2012
DOI: 10.1111/j.1365-2052.2011.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and fine mapping of quantitative trait loci for the number of vertebrae in a White Duroc × Chinese Erhualian intercross resource population

Abstract: The number of vertebrae is associated with body size and meat production in pigs. To identify quantitative trait loci (QTL) for the number of vertebrae, phenotypic values were measured in 1029 individuals from a White Duroc × Chinese Erhualian intercross F(2) population. A whole genome scan was performed with 194 microsatellite markers in the F(2) population. Four genome-wide significant QTL and eight chromosome-wide significant QTL for the number of vertebrae were identified on pig chromosomes (SSC) 1, 2, 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
3
41
0
1
Order By: Relevance
“…In zebrafish, Prox2 is mainly expressed in the brain and involved in eye development [56]. Notably, both Vertnin and Prox2 have recently been proposed as candidates for the number of vertebrae in a White Duroc x Chinese Erhualian intercross, that also carries two different haplotypes for increased teat number [57]. …”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, Prox2 is mainly expressed in the brain and involved in eye development [56]. Notably, both Vertnin and Prox2 have recently been proposed as candidates for the number of vertebrae in a White Duroc x Chinese Erhualian intercross, that also carries two different haplotypes for increased teat number [57]. …”
Section: Discussionmentioning
confidence: 99%
“…A phenotypic correlation of 0.24 between NT and number of thoracic vertebrae has been estimated [42], and a larger number of vertebrae is associated with an increase in carcass length and number of ribs [46], [47]. Thus, the region is of great interest for pig breeders with favourable pleiotropic effects on economically important traits, including mothering ability of the sows due to the increase in NT, and increased pork production per animal due to longer carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…VRTN encodes a potential DNA binding factor and has been described as an essential factor for development of the embryo in different species [48]. Due to its biological function, this gene has been indicated as a candidate gene for number of vertebrae [42], [48], [49]. Recently, Fan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Necks contain cervical and thoracic vertebrae whereas loin cuts include lumbar, sacral and caudal vertebrae. Total number of vertebrae was correlated with total number of vertebrae, rib number, body length and body weight (Borchers et al, 2004;Ren et al, 2012). The QTL on SSC7 centred on VRTN affects mainly thoracic and total number of vertebrae (Mikawa et al, 2005;Ren et al, 2012).…”
Section: Vrtn Polymorphism In Pigsmentioning
confidence: 99%
“…Total number of vertebrae was correlated with total number of vertebrae, rib number, body length and body weight (Borchers et al, 2004;Ren et al, 2012). The QTL on SSC7 centred on VRTN affects mainly thoracic and total number of vertebrae (Mikawa et al, 2005;Ren et al, 2012). According to these studies, the lack of association between VRTN and LC we observed may be explained by the fact that there might be a negative or poor correlation between the length of lean cuts and their weight as, usually, shorter loins have a larger Longissimus dorsi area (Buttazzoni et al, unpublished results).…”
Section: Vrtn Polymorphism In Pigsmentioning
confidence: 99%